TINJAUAN PELAKSANAAN USAHA KESEHATAN SEKOLAH DI SD NEGERI 159/III SEMUMU KECAMATAN DEPATI VII KABUPATEN KERINCI - Jonika Trishandra (Ensiklopedia of Journal, 2019)
This study is based on the reality on the ground, especially in SD N 159 / Semumu Depati VII District of Kerinci regency still low Implementation School Health Unit. The existence of the school health program is very important to support the learning process, in addition to the presence of the UKs will realize a healthy school so convenient for students to gain knowledge. The purpose of this study was to investigate the implementation of UKS program usually refers to UKS: 1) health education, 2) health care, 3) fostering a healthy environment. The method used in this research is quantitative descriptive with a student population of class I to VI SD N 159 / III Semumu Depati VII District of Kerinci district registered the academic year 2014/2015, amounting to 110 people. The sampling technique of this research is Porpusive sampling technique so that the sample is 55 persons, namely grade IV-VI. (50% of the total population). The data collection tool used questionnaire that uses scale Gattmun katagorinya "yes" and "no". While the percentage used to analyze the data. The results showed that the implementation of the UKS in SD 159 / III Semumu Depati VII District of Kerinci regency of sufficient health education category, while health services are included in the category of less, and fostering a healthy school environment is in the category pretty.